Mengkaji Kembali Konsumsi Umat Sebuah Rekonstruksi Interdisiplier terhadap Gaya Hidup Nabi - Ahmad Sahidah (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2012)
This article analizes the issues of   consumtion in Muslim societies and   attempts to reconturct the Islamic   perspective on comsumption. By referring   to the biography of Prophet Muhammad,   the write argues that despite the fact that   there are religious narratives on the way   Muslims should behave in their everyday   life; the Muslim perspective of consump-   tion should also be discussed critically by   utilizing interdisclipnary studies in   humanities and social sciences. The writer   argues that the utilization of modern   social sciences, both religious and secular,   in understanding Islamic tradition, will   bring to new Muslim interpretation on   certain issues such as the theory of   production and consumption in Muslim   societies. It is believed that the Prophet   Muhammad’ life style can be example for   Muslim in modern times, as Prophet was   very concerned with the issues of public   health, cleanliness, and orderliness